Importance of oxyphil cells for 99mTc-sestamibi uptake in primary hyperparathyroidism: a retrospective observational study - Dropmann, Jan Axl; Kleespies, Axel; Fuerst, Heinrich; Kremer, Marcus; Drefs, Moritz; Neuberger, Michael (Nuklearmedizin - NuclearMedicine, 2025)
In patients with primary hyperparathyroidism (pHPT), the importance of oxyphil cells for 99mTc-sestamibi uptake is uncertain.This retrospective observational study of pHPT patients evaluated independent associations between oxyphil cell content (OCC) and preoperative scintigraphic (SC) findings, using logistic regression analyses.We studied 76 patients with pHPT before and after operation. Preoperative SC was able to definitively identify abnormal parathyroid tissue in 47 patients (61.8%). The median relative OCC (postoperative histopathological examination) was 10% (IQR 0.25% – 40%) and the median absolute OCC was 0.09 cm3 (IQR 0.00 – 0.59 cm3). After adjustment for confounders, an iPTH concentration >200 pg/ml and increasing OCC was the only significant independent predictor of a definitively positive SC result (per category of relative OCC: adjusted odds ratio (aOR) 2.40, 95% confidence interval (CI) 1.02 – 5.65, p=0.045).In patients with pHPT, a higher OCC was associated with a significantly higher probability of a clearly positive SC finding.
Keywords: primary hyperparathyroidism; parathyroid scintigraphy; oxyphil cell; parathyroid hormone; Tc99m-sestamibi uptake